Implications of real and nominal shocks on macroeconomic variables under fixed exchange rate Regime: the FTPL approach - Mohamad Feghhi Kashani; Javid Bahrami; mohammad abbasi (اقتصاد باثبات)
In this article, the effects of productivity, foreign prices and oil exports shocks on the main variables including production and consumption were investigated, in a small open economy and in a situation where the country has adopted a policy of stabilizing the exchange rate. In this analytical space, under certain conditions, a cycle between the government and the financial and real sectors is created, which leads to the repeated reduction of the government primary surplus, and thus increases the probability of the government's inability to repay previously issued bonds and decreases the value of government bonds. This process ultimately leads to government debt-overhang, banking crisis and the reduction of total production and Consumption. For this purpose, the literature of "Fiscal Theory of the Price Level" (FTPL) has been used to analyze the performance of the government, which seems to be compatible with the institutional and legal conditions of Iran. According to this theory, the government, in some situations, can become the dominant actor in determining the general price level, and monetary policies are mainly regulated in accordance with the government fiscal policies. The above-mentioned process was implemented in a simple dynamic general equilibrium model that describes the behavior of actors in the economic environment, and the results on the variables of the model were analyzed. As a result, it was observed that the introduced shocks, such as nominal or real, even without any price stickiness and in conditions where domestic goods are priced based on global values, can have detrimental real impacts on key economic variables and public welfare.